Impacts of MicroRNAs Induced by the Gut Microbiome on Regulating the Development of Colorectal Cancer - Xing, Juan; Liao, Yiqun; Zhang, Huan; Zhang, Wenjie; Zhang, Zhilin; Zhang, Jie; Wang, Daorong; Tang, Dong (Frontiers in Cellular and Infection Microbiology, 2022)
Although a dysfunctional gut microbiome is strongly linked to colorectal cancer (CRC), our knowledge of the mediators between CRC and the microbiome is limited. MicroRNAs (miRNAs) affect critical cellular processes, such as apoptosis, proliferation, and differentiation, and contribute to the regulation of CRC progression. Increasingly, studies found that miRNAs can significantly mediate bidirectional interactions between the host and the microbiome. Notably, miRNA expression is regulated by the gut microbiome, which subsequently affects the host transcriptome, thereby influencing the development of CRC. This study typically focuses on the specific functions of the microbiome in CRC and their effect on CRC-related miRNA production and reviews the role of several bacteria on miRNA, including Fusobacterium nucleatum, Escherichia coli, enterotoxigenic Bacteroides fragilis, and Faecalibacterium prausnitzii. Based on the important roles of miRNAs and the gut microbiome in CRC, strategies for modulating miRNA expression and regulating the gut microbiome composition need to be applied, such as bioactive dietary components and fecal microorganism transplantation.